2009
DOI: 10.1080/01674820903212136
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of exercise to alleviate postpartum depressed mood

Abstract: Home-based exercise is a feasible nonpharmacological intervention with the potential to alleviate postpartum depressive symptoms, especially in women with higher initial depressed mood scores as measured by the EPDS. These findings may guide the design of future exercise clinical trials with postpartum depressed women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 61 publications
1
71
0
3
Order By: Relevance
“…This study was part of a randomized trial evaluating the effects of home-based exercise on postpartum depressed mood (PPD) [31].…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a randomized trial evaluating the effects of home-based exercise on postpartum depressed mood (PPD) [31].…”
Section: Methodsmentioning
confidence: 99%
“…One study on postpartum women within 4–38 weeks of childbirth revealed specific exercise facilitated the mother's recovery process (Da Costa et al, 2009). According to research by McIntosh (1993) factors such as lack of support, lack of time, and frequent feeling of isolation could contribute to the mental health and recovery in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show promise and support the positive effects of postnatal MPA as a treatment modality for PPD [42][43][44][45][46][47]; however measuring MPA during the postpartum period fails to include the cumulative effect of exercise throughout pregnancy, which may play a preventative role in the development of PPD.…”
Section: Introductionmentioning
confidence: 99%